Hubungan Status Gizi terhadap Perkembangan Motorik pada Anak Usia 6-24 Bulan - Tuhu Perwitasari; Melda Amalia (Universitas Baiturrahim, 2021)
The quality of human resources is related to the quality of children, where the quality of children today has an impact on the quality of human resources in the future. The number of sufferers of malnutrition and malnutrition is around 28% of the total children under five in Indonesia. About 10% of children under five who suffer from malnutrition and lack of nutrition end up dying. The under-five mortality rate is 37 per 1,000, half of which is due to malnutrition. This study was conducted to determine the relationship between nutritional status and motoric development in children aged 6-24 months. This study used an analytic observational design with a cross sectional approach. The subjects of this research were all mothers and toddlers who came to the low stinger Integrated health-service post (POSYANDU) in the work area of the Aur Duri’s public health center (PUSKESMAS), namely 30. The measuring instruments used were the dacin weight balance, microtoise and KPSP scales. Bivariate analysis using chi-square. The results of the study which is mostly under five year old children in aged 13-24 months and male gender is 36.7%. The most nutritional status (BW / U) in children aged 6-24 months is Good Nutrition with the male gender, namely 53.4%. The development of children aged 6-24 months at most was normal, with 8 male respondents (26.7%). The conclusion yields there is no significant relationship between the levels of nutritional status of children under five years old with the development of children. It is expected that parents will increase stimulations. Health workers and cadres should be included in training so that they can measure progress with the KPSP